Impact of cervical cancer counseling on the attitudes of fertile age women early detection in Padokan Lor Hamlet, Tirtonirmolo Village - Nurul Sya’bin; Warsiti Warsiti (International Journal of Health Science and Technology, 2020)
Cervical cancer is the second most common cancer suffered by women in the world after breast cancer. In developed countries, the incidence of cervical cancer is around 4% of all cancer incidence in women, while in developing countries it reaches above 15% (Emilia, 2010). The purpose of this study was to determine the effect of cervical cancer counseling on the attitude of WUS to early detection (IVA) in Padokan Lor Hamlet, Tirtonirmolo Village. The type of research used is pre-experiment with the design of "one group pretest-posttest". Sampling using purposive sampling technique, the number of samples was 45 respondents. Bivariate analysis was carried out using the WoCoxon test statistical test. The results of Wilcoxon test obtained the value (p = 0,000) less than 0,05. Conclusion, there is an influence of cervical cancer counseling on the attitude of WUS to early detection (IVA) in Padokan Lor Village, Tirtnirmolo Village, 2015.